2003
DOI: 10.1097/01.aud.0000051745.69182.14
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Judgments of Sound Quality in Elderly Hearing Aid Wearers

Abstract: The JSQ appears to be a potentially useful measure of hearing aid outcome, especially when using group data to document the benefits of amplification. Additional efforts should be directed at improving the reliability of the JSQ, however, before application to hearing aid wearers on an individual basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 10 publications
0
7
1
Order By: Relevance
“…For example, Gabrielsson et al (1988) reported that reliability of sound quality ratings using several different scales (e.g., overall impression, clarity, loudness, fullness) were lower in listeners with hearing loss than in listeners with normal hearing. Narendran and Humes (2003) reported that the elderly listeners with hearing loss in their study showed even less reliability in quality ratings compared with the hearing-impaired listeners in the study by Gabrielsson et al (1988). Finally, the listeners with hearing loss in Tan and Moore (2008) showed less reliability in ratings of sound quality for sounds subjected to nonlinear distortion than did listeners with normal hearing.…”
Section: Discussion and Summarymentioning
confidence: 82%
“…For example, Gabrielsson et al (1988) reported that reliability of sound quality ratings using several different scales (e.g., overall impression, clarity, loudness, fullness) were lower in listeners with hearing loss than in listeners with normal hearing. Narendran and Humes (2003) reported that the elderly listeners with hearing loss in their study showed even less reliability in quality ratings compared with the hearing-impaired listeners in the study by Gabrielsson et al (1988). Finally, the listeners with hearing loss in Tan and Moore (2008) showed less reliability in ratings of sound quality for sounds subjected to nonlinear distortion than did listeners with normal hearing.…”
Section: Discussion and Summarymentioning
confidence: 82%
“…D'Onofrio et al (2019) found that hearing-impaired listeners rated the sound quality of aided speech and music with moderate reliability between test-retest conditions. Narendran and Humes (2003) also investigated the test-retest reliability of different sound quality ratings for aided speech and music with hearing-impaired listeners and found that correlations for descriptors most similar to those used in this study (clarity, fullness, loudness, and total impression for aided speech and music) were moderate. These findings suggest that listeners experience similar sound quality when listening to novel stimuli using genre-specific frequencygain shaping to that for listening to identical stimuli for a second time.…”
Section: Generalizability Of Preferred Shapingmentioning
confidence: 80%
“…As shown in experiment 1, we see significant variance in rating judgments even within a single session in a single subject. It is also likely that rating judgments may be difficult for elderly patients showing some memory or cognitive dysfunction 23,24. Given that retinal implants target diseases such as retinitis pigmentosa and macular degeneration, which primarily affect older populations, methods of calibrating the brightness of electrodes that are robust against cognitive and memory decline have a distinct advantage.…”
Section: Experiments 2: Brightness Matchingmentioning
confidence: 99%